Integrasi Nilai-nilai Keislaman dalam Pembelajaran Sains di Madrasah Ibtidaiyah Ma’arif 01 KH. Shiddiq Jember - Siti Hamidahtur Rofi’ah (Childhood Education : Jurnal Pendidikan Anak Usia Dini, 2020)
Abstract: The dichotomy of science between religion and science makes a person only intellectually intelligent, he does not know God, and the role of science is solely for practical purposes. Therefore it is necessary to instill the principles of monotheism in the teaching of general sciences including science, so that religion and science can go hand in hand. The focus of research to be studied is How to integrate Islamic values ​​in science learning in Madrasah Ibtidaiyah Ma'arif 01 KH. Shiddiq Jember. The purpose of this study is to describe the integration of Islamic values ​​in the study of science in Madrasah Ibtidaiyah Ma'arif 01 KH. Shiddiq Jember. This research uses a qualitative approach to the type of case study. Data collection techniques using passive participation observation, in-depth interviews, and documentation. Data analysis techniques using interactive analysis Miles, Huberman, and Saldana. The results of the study that the method of integrating Islamic values ​​in science learning in MIMA 01 KH. Shiddiq Jember by making the Koran and Hadith as a source of knowledge, tracing the verses of the Koran related to Science material. When learning takes place the method used is scientific literacy and discussion to form students who are Ulul Albab. Keyword: Integration, Islamic Values And Science Learning